ANALISIS PENGELOLAAN KELAS OLEH GURU PAK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA VIII SMP NEGERI 1 PARANGINAN TAHUN AJARAN 2017/2018 - Ius Riani Rangkuti (IAKN Tarutung, 2018)
Abstract, This research aims to know analysis of the class management by teacher religion Christian education in improving the learning motivation of the students in grade VIII of SMP Negeri 1 Paranginan in 2017/2018 academic years, with the hypothesis is the class management by teacher religion Christian education can improving the learning motivation. Technique of analyzing data was statistic technique with type of research quantitative descriptive research with 206 population of all students who are Christiant Protestant in grade VIII and 20% from population as much as 53 peoples were selected as the samples taken by random sampling technique. Analyzing data was indicated that test of hyphotesis: tcount≥ttable namely 6.458 1.67. Thus, Ha accepted, the conclusion drawn from this study was the class management by teacher religion Christian education can improving the learning motivation of the students in grade VIII of SMP Negeri 1 Paranginan in 2017/2018 academic years.